2013
DOI: 10.1007/s12178-013-9172-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of femoroacetabular impingement: a systematic review

Abstract: The purpose of this review is to determine if there is a difference in outcomes after: (1) nonsurgical vs surgical treatment of FAI; (2a) surgical dislocation with greater trochanteric osteotomy, (2b) anterior mini-open, (2c) arthroscopic plus mini-open, and (2d) arthroscopic surgery for FAI; (3) difference in complication and re-operation rates; and (4a) labral refixation and (4b) labral debridement for labral injuries. A systematic review of multiple databases was performed after PROSPERO registration and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 46 publications
1
53
0
6
Order By: Relevance
“…21 However, Harris et al reported a BMI of 24.5±2.6 kg/m 2 in a review of more than 2,000 FAI patients, making the results of this study relevant to the future study of FAI with dualfluoroscopy and model-based tracking. 22 Still, the radiation and imaging settings used in our study may not be applicable to overweight or obese individuals. Nonetheless, use of ionizing radiation, especially with regards to CT, needs to be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, Harris et al reported a BMI of 24.5±2.6 kg/m 2 in a review of more than 2,000 FAI patients, making the results of this study relevant to the future study of FAI with dualfluoroscopy and model-based tracking. 22 Still, the radiation and imaging settings used in our study may not be applicable to overweight or obese individuals. Nonetheless, use of ionizing radiation, especially with regards to CT, needs to be carefully evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly low level of evidence case series with broad patient inclusion criteria indicate that the arthroscopic treatment of intra-articular pathologies and correction of bony deformities related to FAI seem to reduce hip pain and improve hip function, with the majority of patients being satisfied with the surgical outcome 5. However, to the best of our knowledge, no published study has compared hip arthroscopy with other non-surgical interventions to establish the true effectiveness of hip arthroscopy for the management of FAI 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…Some systematic reviews have already summarised the current knowledge on patient-reported outcomes after hip arthroscopy in patients with FAI 5 8–12. The large majority of studies included in previous systematic reviews reported hip arthroscopy outcomes with composite scores (eg, Harris Hip Score and Non-Arthritic Hip Scale) 5 8–12.…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al [43] in a comprehensive systematic review reported that statistically significant differences were observed among patients following surgical and non-surgical treatments for FAI, with greater improvement found among patients that underwent surgery. No significant differences were observed between the different surgical techniques used.…”
Section: Outcome Of Surgical Managementmentioning
confidence: 99%